"Pupils should have respect for you, although I have no idea how to achieve this?": The ideals and experiences shaping a teacher's professional identity. Issue 2 (4th March 2019) - Poom-Valickis, Katrin; Löfström, Erika
Abstract: The aim of the study was to understand the development of professional identity of prospective teachers, their ideals and experiences during interactions with their surrounding learning environment, including university studies and pedagogical placement during their 5-year studies. We also aimed at understanding how students with different motivational pathways to teacher education may be supported to explore teaching as a possible career choice. The findings reported in this article emerged primarily from interviews with 13 student teachers at the end of their teacher education programme. Survey responses collected during earlier stages of the study were utilised to provide data about the student teachers' professional development prior to the point of the interviews. The findings of the study point to various concerns and dilemmas, which in turn suggest that student teachers take different identity development routes. The study identified four possible "identity routes" to becoming a teacher. The implications of different identity routes on teacher education are discussed.